Linguistic construction of a winning apology - Raja Ravi Varma, Susanna Bithiah Varma; Paramasivam, Shamala; Nimehchisalem, Vahid (Shahid Chamran University of Ahvaz, 2019)
The study analyzes the apology delivered by the then-democratic Presidential contender in 2007, Senator Barack H. Obama, to the Indian-American community. This apology succeeded in convincing American citizens of Obama’s goodwill and clean political standards, which eventually led him to surpass his chief opponent, Senator Hillary R. Clinton and become the President of the United States. The study employs Searle’s (1969) speech act theory (SAT) and Holmes’s (1990) apology strategies through pragmatics. The study, then, administrates thematic analysis through positive discourse analysis to gain insights from Obama’s leadership values. Findings educate readers on the importance of an apology construction and encourage readers to follow the example of a world-class leader’s values by having an insight into Obama’s leadership.